2012
DOI: 10.3174/ajnr.a3303
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization Transfer Imaging in Premanifest and Manifest Huntington Disease: A 2-Year Follow-Up

Abstract: BACKGROUND AND PURPOSE:MTI is a quantitative MR imaging technique that has recently demonstrated structural integrity differences between controls and patients with HD. Potentially, MTI can be used as a biomarker for monitoring disease progression. To establish the value of MTI as a biomarker, we aimed to examine the change in these measures during the course of HD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 31 publications
0
10
0
1
Order By: Relevance
“…Several studies have addressed MT imaging, yet focusing on the MTR. A reduction of the MTR peak height in gray and white matter in manifest HD compared to healthy controls ( 23 ) has been reported, but no differences between presymptomatic gene carriers and controls. These studies concluded that there is no role for MTR as a biomarker in presymptomatic HD ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have addressed MT imaging, yet focusing on the MTR. A reduction of the MTR peak height in gray and white matter in manifest HD compared to healthy controls ( 23 ) has been reported, but no differences between presymptomatic gene carriers and controls. These studies concluded that there is no role for MTR as a biomarker in presymptomatic HD ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced MT contrast can be symptomatic of disruption of myelin sheath or axonal loss 36,75 . In HD, decreased MT contrast was found in grey matter and white matter of pre-symptomatic gene carriers and HD patients, with correlation between MT loss and disease severity 76,77 . In this study, we reported for the first time MT defects in a mouse model of HD, especially in the septum and in the striatum.…”
Section: Figure 8: a White Matter Tracts Isolated From The Whole Brain Tractography Of A Representative Dataset Using Locally-constrainedmentioning
confidence: 94%
“…In HD patients also, neuronal degeneration occurs first in the striatum [6], then in other areas of the brain [28,76,77]. It is notable that significant loss of basal ganglia volume [78][79][80][81][82][83] and neuron loss [84] have been reported in asymptomatic HD patients. The appearance of inclusions in HD patients also precedes the onset of symptoms and neurodegeneration [4,5,16,85].…”
Section: Neurodegeneration In R6/2 Micementioning
confidence: 99%